Extremal properties of multiparameter selective signals built on the basis of spline-inerpolation - Стрелковская, Ирина Викторовна (Eastern-European Journal of Enterprise Technologies, 2009)
Multiparameter signals for a case of interpolation of their spectral density by cubic spline are considered. Extremal properties of these signals are researched